Dengue and chikungunya: future threats for Northern Europe? - Laverdeur, Justine; Desmecht, Daniel; Hayette, Marie-Pierre; Darcis, Gilles (Frontiers in Epidemiology, 2024)
Arthropod-borne viral diseases are likely to be affected by the consequences of climate change with an increase in their distribution and intensity. Among these infectious diseases, chikungunya and dengue viruses are two (re)emergent arboviruses transmitted by Aedes species mosquitoes and which have recently demonstrated their capacity for rapid expansion. They most often cause mild diseases, but they can both be associated with complications and severe forms. In Europe, following the establishment of invasive Aedes spp, the first outbreaks of autochtonous dengue and chikungunya have already occurred. Northern Europe is currently relatively spared, but climatic projections show that the conditions are permissive for the establishment of Aedes albopictus (also known as the tiger mosquito) in the coming decades. It is therefore essential to question and improve the means of surveillance in northern Europe, at the dawn of inevitable future epidemics.